Decoding the Magic Formula: Navigating the Complex World of Stock Trading - Soetam Rizky Wicaksono; Rudy Setiawan (Universitas Muhammadiyah Ponorogo, 2024)
Stock trading is complicated and risky. Investors' conditions, aspirations, and viewpoints shape their journeys. This article examines stock trading and investing, focusing on Joel Greenblatt's